TRANSKRIPSI AND TRANSLITERASI DARI TEKS TARIKAT PENGAJIAN TUBUH - Azwar, Rezi; Juita, Novia; Nurizzati, Nurizzati (Jurnal Bahasa dan Sastra, 2018)
This research aimed to: (a) present a description of Tarikat Pengajian Tubuh script, (b) present the transliteration form from Arabic-Malay into Latin script of Tarikat Pengajian Tubuh text, (c) present the translation from Malay-Minang into Indonesian language of Tarikat Pengajian Tubuh script. This research is a philology research. The object of his research is the text of the Tarikat Pengajian Tubuh. The method of this research is descriptive method and method of philology research which is adjusted with research stage. At the data collection stage used field study method and literature study method. The results of this research were (1) the complete description of the script, (2) the transcription ofTarikat Pengajian Tubuhtext which can be read and understood by the people in order to know the important of knowing the extent of human body, the creation of a body and its life, and get to know who God is, (3) Tarikat Pengajian Tubuh text had adapted into correct Indonesian Spelling (EBI). Some of Malay’s vocabularies and Minangkabau language’s vocabularies found inTarikat Pengajian Tubuh script were maintained to preserve the purity of the old vocabulary.Keywords: transliteration, translation, text, philology